Guns, butter, and debt: Sovereign creditworthiness and military expenditure. (September 2015) - DiGiuseppe, Matthew
I argue that favorable access to sovereign credit provides governments with greater autonomy to invest in security by allowing political incumbents to relax fixed-budget constraints. Borrowing permits leaders to delay and minimize the macroeconomic and redistributive costs associated with domestic sources of finance. Consequently, leaders of creditworthy states face fewer political costs when increasing military expenditure in response to growing demand or maintaining military expenditure when government revenues fall. A cross-sectional time-series analysis supports two observable implications of the argument. First, creditworthiness is positively associated with military spending with an effect on par with regime type. Second, creditworthiness conditions the effect of external threats on military expenditure, suggesting that poor credit terms constrain the provision of security.